Решите уравнение 5(х-2)^2+6(х-2) =х-2

Решите уравнение 5(х-2)^2+6(х-2) =х-2
Гость
Ответ(ы) на вопрос:
Гость
СПОСОБ 1 5*(х²-4х+4)+6х-12-х+2=0 5х²-20х+20+6х-12-х+2=0 5х²-15х+10=0 х²-3х+2=0 Д=9-4*1*2=9-8=1 х1=3-1\2=2\2=1 х2=3+1\2=4\2=2 Проверка а)х=1 5*(1-2)²+6*(1-2)=1-2 5*1-6=-1 -1=-1 (корень) б)х=2 5*(2-2)²+6*(2-2)=2-2 5*0+0=0 0=0  (корень) СПОСОБ 2 х-2=а 5а²+6а=а 5а²+6а-а=0 5а²+5а=0 5а*(а+1)=0 а=0  или а+1=0 а=-1 подстановка а)а=0 х-2=а х-2=0 х=2 (корень) б)а=-1 х-2=а х-2=-1 х=-1+2 х=1 (корень)
Не нашли ответ?
Ответить на вопрос
Похожие вопросы